Features of anti-land tort - Мілімко, Лариса Василівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2011)
The article is devoted to countering the problem of offenses committed in the sphere of land relations. The most effective way to combat land offenses is the elimination of conditions for performing them.